Business analytics on AIS data: Potentials, limitations and perspectives - Tina Scheidweiler; Carlos Jahn (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: As maritime digitalization progresses, great opportunities for maritime transport arise: the introduction of the AIS opened up a number of possibilities and perspectives for increasing efficiency, automation and cost reduction using business analytics and machine learning in the supply chain and maritime sector
urn:nbn:de:gbv:830-882.054922; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Business; Analytics; Maritime; Traffic